A mixed methods approach for the integration of urban design and economic evaluation: Industrial heritage and urban regeneration in China. Issue 2 (March 2018) - Berta, Mauro; Bottero, Marta; Ferretti, Valentina
This paper presents the early results of a study aimed at experimenting an innovative approach to the design and the evaluation of complex urban transformation processes, based on the combined use of different design strategies and tools. The purpose of the paper is to illustrate, by means of a case study, a multi-level decision aiding process, able to support strategic urban design, with specific reference to regeneration processes for abandoned industrial sites in urban areas. The case study presented in the paper concerns different alternative proposals for the requalification of the former Shougang/Er-Tong mechanical factory in Beijing, China. The choice of a Chinese case study as a field test for an experimentation about mixed methods research approaches in the domain of urban transformation is related to the peculiar emerging conditions of that context, in which huge economic potentials are speeding up the transformation but a substantial lack of cultural and methodological instruments to manage a so fast modification exists. During the design process, three methods in particular have been combined according to a multi-phase design: (i) Stakeholders Analysis, (ii) Multicriteria Analysis, and (iii) Discounted Cash Flow Analysis. Each one of them has been applied in parallel to the evolution of the different design scenarios. The results of the performed study show that mixed methods approaches are a promising line of research in the field of environmental evaluation and urban design. Insights and guidelines for the replication of the proposed methodological approach in other territorial contexts are also proposed.